The revelation incentive for issue engagement in campaigns - Chitralekha Basu; Matthew T. Knowles (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
How do parties choose issues to emphasize in campaigns, and when does electoral competition force parties to address issues important to voters? Empirical studies have found that although parties focus disproportionately on favourable issues in campaigns, they also spend much of the 'short campaign' addressing the same issues - and especially if these are salient issues. We write a model of multiparty competition with endogenous issue salience, where, in equilibrium, parties behave in line with these patterns. In our model, parties' issue emphases have two effects: influencing voter priorities, and also informing voters about their issue positions. Thus, parties trade off two incentives when choosing issues to emphasize: increasing the importance of favorable issues ('the salience incentive'), and revealing their positions on salient issues to sympathetic voters ('the revelation incentive'). The relative strength of these two incentives determines how far elections constrain parties to respond to voters' initial issue priorities.
Keywords: D72; D83; 330; Electoral competition; Issue salience; Issue selection; Party strategy; Campaigns